Considering the reality of hegemonic tendencies: English and linguistic diversity - Miguel Mantero (Indonesian JELT, 2019)
This paper aims to analyze the commodification aspect of dominant languages, in particular, English, while looking into linguistic diversity as a commodity in its own right. In order to illustrate multilingualism as a valuable commodity in itself, we mention Immersion Programs in the US and the increasing recognition of the importance of being proficient in languages other than English, for educational, personal, economic and national security reasons. This research also aims to look into some aspects of the delicate issue of English being strengthened over the weakening of thousands of local languages and cultures. Some arguments are provided in order to illustrate the fact that ‘global English’ represents special politico-economic interests that cannot meet the needs of the people whose languages and cultures are being subjugated by the imperialistic and capitalist ideologies of the spread of English. Unless local language policies are elevated on political agendas, globalization language policies will remain insensitive to the irreplaceable value of linguistic diversity, along with the real needs of citizens from all over the world.